Human systems engineering and design : proceedings of the 1st International Conference on Human Systems Engineering and Design (IHSED2018) : Future Trends and Applications, October 25-27, 2018, CHU-Université de Reims Champagne-Ardenne, France /: proceedings of the 1st International Conference on Human Systems Engineering and Design (IHSED2018) : Future Trends and Applications, October 25-27, 2018, CHU-Université de Reims Champagne-Ardenne, France. ([2019]) - Unknown
No abstract available